Encyclopedia of the Cold War - Dijk, Ruud van. (New York : Routledge, 2008)
Between 1945 and 1991, tension between the USA, its allies, and a group of nations led by the USSR, dominated world politics. This period was called the Cold War--a conflict that stopped short to a full-blown war. Benefiting from the recent research of newly open archives, the Encyclopedia of the Cold War discusses how this state of perpetual tensions arose, developed, and was resolved. This work examines the military, economic, diplomatic, and political evolution of the conflict as well as its impact on the different regions and cultures of the world. Using a unique geopolitical approach that will present Russian perspectives and others, the work covers all aspects of the Cold War, from communism to nuclear escalation and from UFOs to red diaper babies, highlighting its vast-ranging and lasting impact on international relations as well as on daily life. Although the work will focus on the 1945-1991 period, it will explore the roots of the conflict, starting with the formation of the Soviet state, and its legacy to the present day--Publisher's description.
V. 1. A-J; Index -- v. 2. K-Z; Index.
Includes bibliographical references and index.
Keywords: Cold War -- Encyclopedias; Encyclopedia; encyclopedias; Encyclopedias